Impact of Artificial Intelligence on Assisted Robotics for People with Disabilities: A Systematic Review - Caffo Villalobos, Maria de Fatima (2025)
This paper presents a systematic review of the applications of artificial intelligence (AI) in assistance robots for people with disabilities, aiming to evaluate their impact on users' quality of life. The research examines various AI applications, analyzing their effectiveness and progress in areas such as mobility, social interaction, physical rehabilitation, and cognitive support. An exhaustive search was conducted in academic databases, selecting relevant studies detailing the implementation of these technologies in assistive devices.  Twenty-one key studies were identified and analyzed, demonstrating that AI-assisted robots have significantly enhanced the mobility and autonomy of people with disabilities while also contributing to their emotional and social well-being. However, several persistent gaps and challenges were identified, including the affordability of technologies, the customization of solutions, and ethical concerns regarding human-robot interaction. The findings of this work highlight AI's potential to transform the lives of people with disabilities but also underline the need for progress in personalizing solutions and addressing social and economic barriers. The final conclusion emphasizes the importance of further research in areas such as AI ethics and the cultural adaptation of robots to enhance their accessibility and effectiveness for all users.